PERSEPSI PENGUNJUNG TERHADAP DESTINASI WISATA ALAM ULEM-ULEM SPTN II RESORT TETEBATU TAMAN NASIONAL GUNUNG RINJANI - Abdullah, Baiq Amanda Esya; Markum, Markum; Setiawan, Budhy (Fakultas Pertanian Universitas Mataram, 2024)
Visitor perception is interpreted as an assessment or view of visitors to a tourist destination, which means a tourist destination must improve the quality of the destination for the better in order to get a positive perception. Therefore, visitor perceptions need to be examined to find out direct responses to Ulem-Ulem's Ecotourism Destinations. This can provide input and evaluation to the management of the Ulem-Ulem Ecotourism Destination as an effort to improve and recommend for the manager for visitor satisfaction. This research was carried out in Ulem-Ulem Nature Tourism with the aim of finding out how visitors perceive Ulem-Ulem Nature Tourism. The method used in this study is the descriptive method. Research data collection is carried out by observation, interviews, literature studies, and questionnaires. Determination of respondents using accidental sampling technique, with a total of 53 respondents. Data analysis using the Likert scale method with the provision of criteria limitations Very Good if the score interval is >116-140, Good if the score interval is >89-115, less good if the score interval is >62-88, and not good if the score interval is 35-61. The results of such analyses are presented in the form of tables. Based on the results of the study, the values for the variables Attraction, Accessibility, Ancillary services, and Price were in the good category with consecutive score values, namely (23.49), (21.57), (22.08), (22.38), (24.04).